Digital Citizenship Dimensions in Arabic Language Curricula for Secondary Stage from View of Its Teachers in Makkah Al Mukarramah: Qualitative and Quantitative Study - Masoud, Afnan Omar; Al-Nimri, Hanan Sarhan (Journal of Curriculum and Teaching Methodology, 2023)
The secondary stage, from the point of view of its teachers. The study relied on the mixed approach and the interview was used as a tool for collecting qualitative data from the study sample, which consisted of (7) female teachers. While the questionnaire was used as a supporting tool to collect quantitative data from the study sample, which consisted of (69) female teachers. Among the most important results that were reached: The concept of digital citizenship was represented by Arabic language teachers in three main categories: explicit and explicit use, implicit and unconscious use and denunciation of the use of digital citizenship in teaching Arabic. The study also revealed an average level of inclusion of the dimensions of digital citizenship in the Arabic language curricula. As the overall questionnaire obtained an arithmetic mean (61.06); That is, with a degree (some extent available), while the results showed a high degree of agreement between the two study samples for the availability of the two dimensions (access and digital etiquette) in the Arabic language curricula and a medium degree for the two dimensions (communication and digital rights) and a low degree for the availability of the dimensions (Health, culture, and digital security).